The very beginning of the Serbian social security law in the Saint Sava's nomocanon - Božović Bojan V. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2018)
Despite the fact that freedom of labor as an assumption of social public policy has emerged only in capitalist society, the article indicates that certain initial elements- seeds of social security law can be recognized even in ancient and middle ages. In accordance with that context, the subject of this research is the largest middle age codex in Serbia, the Saint Sava's Nomocanon, its provisions based on the idea of social justice, provisions aimed at fulfillment of social requirements and used as a response to social risks and social cases, as well as institutionalization of special protection of women, children and family. That said brings us to the conclusion that the observed provisions of the Saint Sava's Nomocanon, the very ones that promote Christian doctrine of social justice and that contain a line of ethical requirements which influence the process of moralization of social relations, are essentially identical with the idea of social justice of the modern state of welfare within the European social model, as well as with the emancipation role of social security law and that the legal institutions of the Saint Sava's Nomocanon are the very beginning of the Serbian social security law.